Leadership Role in Higher Education for Sustainable Development Goal: Reflections from Tribhuvan University - Shrestha, Rupa (Curriculum Development Journal, 2024)
This study aims to seek the answer to the question of how to lead higher education institutions to incorporate sustainable development goals_4.7, especially to work as transformation agencies. It applied the qualitative research methodology to conceptualize the underlying educational mechanism. It generates facts from open ended questions and policy documents. The analysis is based on in-depth interviews with the university’s high-ranking officials. The result reveals that central-level policy and TU Vision are yet to be embedded to acknowledge the goal in these three areas: research, curriculum revision on meeting labor market demands, and collaboration. Therefore, the incorporation of the goal into the university’s system is becoming an extra project. Moreover, it explores that institutional memory and transforming the national priority into a university extensively depends on the leader’s role. As none of the executive leaders express the concept of goal in the higher education system, it is revealed that existing leadership practices are unstructured. This study raises the issue regarding the role of leadership and existing leadership practices in fostering SDG culture. This study will be one of the research documents for sensitizing leaders to improve higher education institutions’ national and global arena. This research is Nepal’s first study of its type with a broad understanding of the context and concept of Sustainable Development Goals at Tribhuvan University from the aspect of leadership.